A Comparative Study of the Dynamic-Mechanical Properties of Styrene Butadiene Rubber/Epoxidized Natural Rubber Dual Filler Nanocomposites Cured by Sulfur or Electron Beam Irradiation. Issue 7 (3rd July 2019) - Ahmadi-Shooli, Sima; Tavakoli, Mitra
Abstract: The properties of (50/50 wt%) styrene butadiene rubber/epoxidized (50%) natural rubber (SBR/ENR50) blends containing nanoclay (NC, 5 or 10phr) without and with carbon black (CB 20phr) cured by sulfur or by electron beam (EB) irradiation (50 and 100kGy), were compared. A sulfur cured compound containing 35phr CB was prepared as a reference sample. Dynamic mechanical thermal analysis (DMTA) indicated that the sulfur cured sample containing 10phr NC and 20phr CB and the 100kGy irradiated sample with 5phr NC and 20phr CB had higher crosslink density, storage modulus, and tensile strength, and less loss factor and loss modulus, compared to the reference sample. Scanning electron microscopy (SEM) images of cryo- fractured surfaces confirmed the DMA and crosslink density results. We suggest a light weight 100kGy irradiated sample containing the lowest amount of NC and 20phr CB with a uniform distribution of the –C–C– bonds crosslinks, for high thermal stability applications and also for passenger cars tire treads, for its ice grip and wet skid properties especially for icy and wet roads, with improvements of 23% and 20%, respectively as compared to the reference sample.